From description to explanation: An empirical exploration of the African‐American pipeline problem in STEM. Issue 1 (2nd May 2015) - Brown, Bryan A.; Henderson, J. Bryan; Gray, Salina; Donovan, Brian; Sullivan, Shayna; Patterson, Alexis; Waggstaff, William
Abstract: We conducted a mixed‐methods study of matriculation issues for African‐Americans in the STEM pipeline. The project compares the experiences of students currently majoring in science ( N  = 304) with the experiences of those who have succeeded in earning science degrees ( N  = 307). Participants were surveyed about their pipeline experiences based on theories that are commonly used to explain matriculation issues. The results of the study revealed that although both groups recognized the major role of race in their experiences, the primary factor distinguishing between students and professionals was their sense of Alignment with their respective community and their different experiences with subtle forms of racism ( Microaggressions ). African‐American scientists were far more likely to report a weak sense of belonging to their community and were far more likely to report subtle encounters with racism. By contrast, African‐American science students were more likely to feel comfortable with the science community and less likely to report subtle racist encounters. The findings of this study are indicative of the pervasive impact of racial bias and conflict as a gatekeeper in providing access to science careers. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 53: 146–177, 2016.